2008
DOI: 10.2353/ajpath.2008.070897
|View full text |Cite
|
Sign up to set email alerts
|

Excess FGF-7 in Corneal Epithelium Causes Corneal Intraepithelial Neoplasia in Young Mice and Epithelium Hyperplasia in Adult Mice

Abstract: We hypothesized that human ocular surface squamous neoplasia (OSSN) may result from the continuous growth stimulation of corneal epithelial progenitor cells. In the present study, we analyzed the effects of excess fibroblast growth factor-7 (FGF-7) on both the proliferation and differentiation of corneal epithelium in a novel Krt12-rtTA/tet-O-FGF-7 double transgenic mouse model in which cornea-specific FGF-7 overexpression is achieved by doxycycline (Dox) treatment. When such adult mice were exposed to Dox, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…We have demonstrated that forced expression of stabilized E3-catenin in the differentiated corneal epithelium can cause tumorigenesis. The phenotypes are similar but not identical to those observed previously in Dox-treated Krt12 rtTA/rtTA /tetO-FGF-7 mice, which also displayed hyperplastic nodules on the corneal surface (Chikama et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We have demonstrated that forced expression of stabilized E3-catenin in the differentiated corneal epithelium can cause tumorigenesis. The phenotypes are similar but not identical to those observed previously in Dox-treated Krt12 rtTA/rtTA /tetO-FGF-7 mice, which also displayed hyperplastic nodules on the corneal surface (Chikama et al, 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Alterations in cell cycling within the limbal area can cause abnormal maturation of the conjunctival and corneal epithelium, and lead to the formation of CIN. In addition, human papilloma virus 16 (HPV16) and/or long-term UVB exposure are known to be the major risk factors associated with human OSSN (Scott et al, 2002; Kiire and Dhillon, 2006) (Chikama et al, 2008). In this tumor model, we found -catenin nuclear translocalized in hyperplastic corneal epithelial cells upon Dox induction.…”
Section: Introductionmentioning
confidence: 69%
“…The FGF-7/FGFR signaling is likely the hub that integrates the input through UVB and HPV with the genesis and formation of OSSN (Figure 2). This may explain why excess FGF-7 caused OSSN phenotype in the Dox-treated Krt12 rtTA/rtTA /tet-O-FGF-7 bi-transgenic mouse model (Chikama et al, 2008). Fig.…”
Section: Fgf-7 Over-expression and Ocular Surface Carcinogenesismentioning
confidence: 99%
“…For example, over-expression of FGF-7 driven by A-crystalline promoter, which is activated in mouse lens at E11.5, resulted in the suppression of cornea-type epithelial differentiation and the induction of ectopic lacrimal gland formation in the corneas of the transgenic mice Govindarajan et al, 2000;Lovicu et al, 1999). In order to understand such an influence at a later stage when epithelial cells have undergone corneal type epithelial differentiation, we developed a Krt12 rtTA/rtTA /tetO-FGF-7 bi-transgenic mouse line in which over-expression of FGF-7 by Dox induction caused squamous cell carcinoma of the cornea resembling OSSN in human (Chikama et al, 2008). Less is known, however, about the signaling pathways by which FGF-7 mediates control of corneal epithelial cell proliferation.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Recently, Chikama et al demonstrated in transgenic mice lines that upregulation of FGF-7 signalling pathway(s) may be common in tumorigenesis derived from limbal stem cells that undergo oncogenic transformation by insults, such as long-term ultraviolet B (UVB) exposure, infection of human papilloma virus (HPV) and human immune deficiency virus (HIV), and cigarette smoking, etc. [2].…”
Section: Introductionmentioning
confidence: 99%